Oribatella (Acari, Oribatida, Oribatellidae) of eastern North America - Behan-Pelletier, Valerie M. (Zootaxa, 2011)
The oribatid mite genus Oribatella (Oribatellidae) includes 107 species worldwide, with 13 species reported for eastern North America. Herein, I describe six new Oribatella species from eastern North America: O. flagellata sp. nov., O. jacoti sp. nov., O. nortoni sp. nov., O. metzi sp. nov., O. texana sp. nov., and O. transtriata sp. nov. Oribatella metzi and O. nortoni are described on the basis of adults and immatures. The deutonymph and tritonymph of O. metzi lack dorsocentral setae dm and dp, and the diagnosis of the genus is expanded to accommodate these newly described immatures, and also newly described adult characters. I provide expanded, detailed diagnoses for previously described species of eastern North America: Oribatella arctica Thor, 1930, O. brevicornuta Jacot, 1934, O. dentaticuspis Ewing, 1910, O. gigantea Berlese, 1916, O. mediocris Berlese, 1916, O. minuta Banks, 1896, O. plummeri Jacot, 1934, O. pusilla Berlese, 1916, O. quadridentata Banks, 1895, O. reticulata Berlese, 1916, O. reticulatoides Hammer, 1955 and provide new distribution records where available. I question the specific status of O. extensa Jacot, 1934, and consider records of O. sexdentata Berlese, 1916 from eastern North America to be doubtful. Oribatella quadricornuta (Michael, 1880) is confirmed to occur in eastern Canada. Finally, I give a key to adults of the 18 species of Oribatella now known from eastern North America.